Where and What: Two Experiments for Dualism - Bucci, Andrea (Journal of NeuroPhilosophy, 2022)
In 2007, two experiments that have now become very famous have appeared in the neuroscientific literature. With over of one thousand of citation, that moved neuroscientist to speculate about the self- representation and other conscious phenomena and to create new experiments, Henrik Ehrsson and Bigna Lengenhagger produce in two studies out of the body experiences in healthy subjects. The literature reports this kind of experience as consequence of neurological disease or drug use. In this article, I will prove that the where, and the what, of the out of the body experience and the normal experience are something different from the bodily one and I will argue in favor of some kind of dualism and, in particular, a dualism called property dualism.